Warming and phosphorus enrichment alter the size structure and body stoichiometry of aquatic gastropods - Wang, Tao; Zhang, Peiyu; Zhang, Huan; Wang, Huan; Su, Xiyang; Zhang, Min; Xu, Jun (Frontiers in Ecology and Evolution, 2022)
Aquatic gastropods are important integral components of the macroinvertebrate community in freshwater ecosystems and play key roles in freshwater ecosystems by contributing to biodiversity, nutrient cycling, and water quality. However, the variation of aquatic gastropods’ community size structure under the combined effects of warming and nutrient enrichment remains largely unknown. Here, we present the results of an outdoor mesocosm experiment examining the interaction of warming (a 4.5 °C increase in mean temperature above ambient conditions) and nutrient enrichment (phosphorus addition) on the community dynamics, size structure and stoichiometric traits of aquatic gastropods. For community dynamics, Bellamya aeruginosa was the dominant species in the gastropod community during the experiment. Our results showed that phosphorus enrichment alone had a positive effect on the total abundance and biomass of gastropods, as well as the abundance and biomass of B. aeruginosa. Warming alone only produced a positive effect on total abundance. However, the combined effects of warming and phosphorus enrichment produced negative effects on the biomass and abundance of the whole gastropod community and the dominant gastropod species (B. aeruginosa). The body mass of B. aeruginosa increased because of warming, whereas the body size of the gastropod community negatively responded to warming. Phosphorus enrichment alone had no remarkable effects on body mass. The combined effects of warming and phosphorus enrichment produced a negative effect on the body mass of the whole community owing to composition species shift but had no substantial effect on the body mass of B. aeruginosa. Hence, the response levels between the gastropod community and the dominant population had remarkable differences. For body stoichiometric traits, warming or phosphorus enrichment alone produced positive effects on the nitrogen and phosphorus contents of B. aeruginosa. The combined effects caused negative effects on the contents of the two elements. The ratio of nitrogen to phosphorus was only decreased by the effects of warming alone. The shift in dominant species at the whole gastropod community level caused by warming and phosphorus enrichment may result in more complex and unpredicted consequences through cascade effects on the structure and function of freshwater ecosystems.